Polygenic control of idiopathic generalized epilepsy phenotypes in the genetic absence rats from Strasbourg (GAERS). - Rudolf, G; Bihoreau, M; Godfrey, R; Wilder, S; Cox, R; Lathrop, M; Marescaux, C; Gauguier, D (2004)
PURPOSE: Generalized nonconvulsive absence seizures are characterized by the occurrence of synchronous and bilateral spike-and-wave discharges (SWDs) on electroencephalographic recordings, concomitant with behavioral arrest. The GAERS (genetic absence rats from Strasbourg) strain, a well-characterized inbred model for idiopathic generalized epilepsy, spontaneously develops EEG paroxysms that resemble those of typical absence seizures. The purpose of this study was to investigate the genetic control of SWD variables by using a combination of genetic analyses and electrophysiological measurements in an experimental cross derived from GAERS and Brown Norway (BN) rats. METHODS: SWD subphenotypes were quantified on EEG recordings performed at both 3 and 6 months in a cohort of 118 GAERS x BN F2 animals. A genome-wide scan of the F2 progenies was carried out with 146 microsatellite markers that were used to test each marker locus for evidence of genetic linkage to the SWD quantitative traits. RESULTS: We identified three quantitative trait loci (QTLs) in chromosomes 4, 7, and 8 controlling specific SWD variables in the cross, including frequency, amplitude, and severity of SWDs. Age was a major factor influencing the detection of genetic linkage to the various components of the SWDs. CONCLUSIONS: The identification of these QTLs demonstrates the polygenic control of SWDs in the GAERS strain. Genetic linkages to specific SWD features underline the complex mechanisms contributing to SWD development in idiopathic generalized epilepsy.